Analysis of Products in Beijing Cultural Tourism Market - PAN, Yuyan; Nedelea, Alexandru Mircea (Ecoforum Journal, 2019)
Through the analysis of the market mix, especially the products and promotion components, we can notice that Beijing’s cultural tourism provide tourists with cultural attractions, events, big quantity of accommodation choices and quite well-built infrastructures with different means of promotion, such as social media, large-scale event (mostly for overseas promotion), online websites and mobile, collaborating with other institutions and organizations, etc. The USP of Beijing cultural tourism is suggested to be the cultural heritages and “Peking” elements, which represent the unique identity of Beijing and differentiate it from other destinations.